EFFECTS OF MANGOSTEEN SKIN GEL EXTRACTS ON INCREASING THE NUMBER OF FIBROBLASTS IN THE HEALING PROCESS OF RATS PERIODONTITIS - Adisty restu Poetri; Anggun Feranisa; Adhiatarika Rismadianti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Periodontitis is one of the most common periodontal diseases in Indonesia. Inflammation and the bacteria that cause periodontitis can be treated by providing additional therapy in the form of a gel by the dentist. Mangosteen peel extract gel contains xanthones which function as antibacterial and anti-inflammatory that will accelerate the inflammatory phase. This study aims to determine the effectiveness of a gel made from mangosteen peel extract to increase the number of fibroblast cells on the healing process of periodontitis in Wistar rats.Methods: This is an experimental laboratory with post test only design. The treatment group composed of 50% mangosteen peel extract gel, 75% mangosteen peel extract gel, 25% metronidazole gel, and metronidazole plus mefenamic acid gel which were applied to Wistar rats after periodontitis induced.Results: The research data were analyzed by One Way ANOVA and exhibited a significance score of p = 0.000 (p<0.05) which indicated a significant difference. In the inter-group test with Bonferroni post hoc, it was found that there was no significant difference between the 75% mangosteen peel extract gel group and 25% metronidazole gel group with a score of p = 0.709 (p>0.05).Conclusion: The conclusion of this research showed that mangosteen peel extract gel was effective in increasing the number of fibroblast cells in the recupiration process of periodontitis